2D versus 3D MFI zeolite: The effect of Si/Al ratio on the accessibility of acid sites and catalytic performance. (June 2018) - Wei, Ruicong; Yang, Hong; Scott, Jason Anthony; Aguey-Zinsou, Kondo-Francois; Zhang, Dongke
Abstract: Through the synthesis of 2D MFI zeolite samples of Si/Al ratio ranged from 13 to 74 with inter-crystalline mesoporosity and their reference 3D counterparts, we have systematically studied and revealed the impact of Si/Al ratio on the inter-dependence of core intrinsic properties of structural porosity and acidity. It is apparent that mesopores in the 2D MFI zeolite play a critical role, dictating the accessibility and distribution of specific acid sites. It was found that, compared to their 3D counterparts, the 2D samples possess a three-times larger accessible surface area owing to the mesopores. Although having a slightly lower total number of acid sites, the 2D samples enjoy a higher percentage of accessible strong acid sites and weak Lewis acid sites. Consequently, in three selected liquid phase reactions, which had different acidity demands and molecular diffusion constraints, the 2D samples demonstrated much higher catalytic activities and resistance to deactivation. This study has, for the first time, established the relationship between Si/Al ratio and acidity for the 2D MFI zeolite, thus enabling rational selection of a Si/Al ratio for a targeted application. Graphical abstract: Highlights: Significant volume of mesopores generated in 2D MFI zeolites synthesized. Three times higher external surface area achieved in 2D than 3D MFI zeolites. More than 80% accessible strong acid sites in 2D MFI zeolites. Dependence of acidity on Si/Al ratios in 2D MFI zeolites revealed. Superior catalytic activity enabled in 2D than 3D MFI zeolites.